Anatomy of original research article and reporting checklists - M V Sruthi (Kerala Journal of Ophthalmology, 2024)
Writing a manuscript requires a lot of time and skill. The manuscript structure and reporting checklists play an important role for authors to complete the manuscript in a timely manner. This article presents the most salent points, highlights the usual mistakes to be avoided and suggests useful tips for writing a good manuscript.